The transmission dynamic of Madariaga Virus by bayesian phylogenetic analysis: Molecular surveillance of an emergent pathogen. (July 2019) - Benvenuto, Domenico; Cella, Eleonora; Fogolari, Marta; De Florio, Lucia; Borsetti, Alessandra; Donati, Daniele; Garilli, Francesco; Spoto, Silvia; Ceccarelli, Giancarlo; Angeletti, Silvia; Ciccozzi, Massimo
Abstract: Madariaga Virus (MADV) is an emergent Alphavirus of the eastern equine encephalitis virus (EEEV) strain complex causing epizootic epidemics. In this study the genetic diversity and the transmission dynamics of Madariaga virus has been investigated by Bayesian phylogenetics and phylodynamic analysis. A database of 32 sequences of MADV group structural polyprotein were downloaded from GenBank, aligned manually edited by Bioedit Software. ModelTest v. 3.7 was used to select the simplest evolutionary model that adequately fitted the sequence data. Neighbor-joining tree was generated using MEGA7. The phylogenetic signal of the dataset was tested by the likelihood mapping analysis. The Bayesian phylogenetic tree was built using BEAST. Selective pressure analysis revealed one positive selection site. The phylogenetic trees showed two main clusters. In particular, Lineage II showed an epizootic infection in monkeys and Lineage III, including 2 main clusters (IIIa and IIIB), revealing an epizootic infection in humans in Haiti and an epizootic infection in humans in Venezuela during the 2016, respectively. The Bayesian maximum clade credibility tree and the time of the most common recent ancestor estimates, showed that the root of the tree dated back to the year 346 with the probable origin in Brazil. Gene flow analysis revealed viral exchanges between different neighbor countries of South America. In conclusion, Bayesian phylogenetic and phylodynamic represent useful tools to follow the transmission dynamic of emergent pathogens to prevent new epidemics spreading worldwide. Highlights: Bayesian phylogenetic analysis of Madariaga virus applied to epidemic strains. Selective pressure, phylogenetic, phylogeographic and gene flow analysis of Madariaga virus epidemic strains. Transmission dynamics of Madariaga virus in South America countries. Molecular surveillance of epidemic strains as preventive measure.